Perlindungan Terhadap Produktivitas Hartadalam Sistem Kewarisan Islam (Analisis Terhadap Maqasid Asy-Syari’ah Dan Kalkulasi Fara’id) - Indra Indra (Universitas Muhammadiyah Sumatera Utara, 2019)
Islamic inheritance law is one of the most interesting topics to be studied because the Republic of Indonesia is a country with a population that is predominantly Muslim, in addition to the many disputes caused by Islamic inheritance law it is also the duty of academics to study this issue so that later it can become a source law in the future. On this occasion the author will examine or discuss how to protect productivity of Islamic inheritance, productivity means that something can be produced which of course the result is the right of one heir or another heir has the same rights. This will be studied using two theories from two different but closely related disciplines, Jurisprudence and other Jurisprudence. First, the method of istiṣlāḥiyyah which refers to maqāṣid ash-syarī‘ah hifẓ al-māl. Second, the istiqrā method or analysis of the farā‘iḍ calculation theory in the fiqh of the four schools.